The Analogous Writer: Literary Evolution in Modernist Virginia Woolf - Hall, Andrew (MacEwan University Student eJournal, 2016)
Some of Virginia Woolf's writing is analytical of the literary world, including its history and processes. Woolf's essay "Modern Fiction" and short story "Solid Objects" analyze and criticize modern writing and can be seen as doing so within similar contexts, albeit in different modes. The main character of "Solid Objects" is arguably representative of Woolf's feelings, made clear in "Modern Fiction" of where modern writing is in the midst of going.